The Influence of Learning Interest on History Learning Outcomes of Senior High School Students at Al-Khairaat Kalukubula - Moh. Adzan; Misnah; Minarni Nogtji; Suyuti (Kirana Publisher (KNPub), 2026)
This study aims to determine the influence of learning interest on the history learning outcomes of students at SMAS Al-Khairaat Kalukubula. The method used is quantitative with an explanatory design. Data were collected through a learning interest questionnaire and documentation of history midterm exam scores. The results of simple linear regression analysis show that learning interest has a significant effect on history learning outcomes, with a coefficient of determination of 86.4%. The conclusion of this study confirms that learning interest is a dominant factor supporting the improvement of student learning outcomes in history subjects.